Local history organizations in the study and preservation of the native language and ethnoculture of the Chuvash in the 1920s - Tikhon S. Sergeev; Ekaterina V. Agaeva (Publishing house "Sreda", 2023)
The establishment of the Soviet power on the territory of the Russian empire led to a new system of values, activation of the population in all fields of the social life. In the sphere of museum building in the 1920s a noticeable role was played by such public scientific and educational associations as the Society for the Study of the Local Territory in Cheboksary (1921-1931) and the Society for the Study of Chuvash Culture in Moscow (1927-1931). The main aim of the article is to reveal the history of the formation and work of these organizations. The material is presented chronologically. Having established close contacts with scientific institutions throughout Russia and with famous scientists, the local history organizations with a wide network of branches and cells promoted an in-depth study and development of the economy and culture of the Chuvash region and the spiritual culture of the Chuvash, half of whose population lived outside the territory of the autonomy. The special attention these societies paid to the development of the native language and culture of the Chuvash people that allowed the Chuvash people to realize their national identity. During the first decade of the Chuvash Soviet autonomy some successes in the formation of local lore as a science were achieved. On the territory of Chuvashia local history institutions and organizations made a significant contribution to the study of nature, economy, productive forces of the region, as well as the spiritual life of the people. In this period it was the Society for the Study of the Local Territory in Cheboksary and the Society for the Study of Chuvash Culture in Moscow that promoted the preservation and development of the Chuvash language.